Electrical and optical properties of Ga-doped ZnO thin films deposited by DC magnetron sputtering - Lukman Nulhakim; Monna Rozana; Brian Yuliarto; Hisao Makino (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2020)
The electrical and optical properties of Ga-doped ZnO (GZO) thin film prepared by direct current (dc) magnetron sputtering were investigated. The GZO thin film was deposited on a glass substrate at a substrate temperature (Ts) of room temperature (RT), 150 °C, and 200 °C using DC power of 100 W and an Ar gas flow rate of 450 sccm. The thickness of films was maintained at about 200 nm by controlling the deposition rate of about 12.5 nm/minute. The result showed that the electrical properties improved with increasing Ts. The films deposited at Ts of 200 °C showed the lowest resistivity, highest hall mobility, and carrier concentration compared to other Ts. The average transmittance of the films in the visible range (380-750 nm) was approximately 86.04%. The value of the optical band gap (Eg) was approximately 3.8 eV. The results suggested that GZO films deposited by DC magnetron sputtering at Ts of 200 °C can be applied to transparent conducting oxide (TCO) as an electrode in optoelectronic applications such as solar cells, LEDs and display technology.